The Growth of ICT indicators in the Digital Economy of Uzbekistan (Eurasian Research Bulletin, 2022)
The article scrutinizes the latest work and research on the digital economy and its core base – ICT infrastructure. Moreover, the digital economy scope of Uzbekistan has been evaluated based on national and international indica-tors in depth. The article concludes that accelerating the process of digital transformation is inevitably urgent despite the annual growth of national and international scores.